Studi Komparatif Penggunaan Metode Diskusi Dan Metode Ceramah Dalam Pembelajaran Ips Di SMP Negeri 2 Indrajaya - Yusrita Maulisa; Darmi Darmi; Maisura Maisura (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2026)
This study aims to determine the effectiveness of the discussion method compared to the lecture method in improving students' understanding of Social Studies at SMPN 2 Indrajaya. The background of the problem is the low student learning outcomes due to the dominance of conventional teaching methods. This research employs a quantitative approach with a quasi-experimental design involving class VIII A as the experimental group and class VIII B as the control group, each consisting of 26 students. The sampling technique used was purposive sampling. The analysis results showed that the Z-count (5.324) was greater than the Z-table (2.957), indicating a significant difference between the two methods. The average N-Gain score of the experimental class was 80.38% (high category), while the control class obtained 76.35% (medium category). Thus, the discussion method is proven to be more effective and has a significant impact on improving student learning outcomes.